Institutional participation of the teachers at the general meeting - González Álvarez, María (Avances en Supervisión Educativa, 2019)
The aim of this paper is to learn, in the opinion of non-university teachers, about the importance of the teachers general meetingcompetences for the proper working of the school  and the quality of the education, as well as the attention and dedication spent on these competences. . To carry out an exploratory analysis, we have written a specific protocol that was filled in by 2334 teachers from the different stages and /or studies and autonomous communities. The staff highly values  the importance of these competences and the appropriation off he attention and dedication by the staff. There are differences regarding sex, ownership of the school and stages and  studies. It is convenient to continue analyzing the importance given by  the teaching staff  to these competencie as well as their fulfillment. The initial and permanent training must consider the involvement of the teachers in the participative structure of the school.
Keywords: Teachers participation; teachers general meeting competencies; sex; ownership of the school; teachers training; teachers general meeting